2021
DOI: 10.51791/njap.v15i.1220
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Body Weight and Some Egg Production Traits in a Strain of Commercial Layer

Abstract: Fifty 28 weeks old layers were reared in individual cages for 9 Weeks to detect the effect weight has on some production traits. Body Weight was positively though non- significantly (P.0.05) correlated with egg number, egg weight and negatively with Shell thickness (r =-0.12) and egg index (r=-0.15). Estimates of optimum 28-week body weights, as determined from second-degree (quadratic) equations, indicated that for satisfactory performance a body weight range of 1728 to 1814g is required, Breeding and good ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
1
0
1
Order By: Relevance
“…The association between body weight and egg weight was similar to the findings of [15] who observed a fairly high association between egg production and weight gain in the Black and Pearl Guinea fowl. This means that point of lay does not terminate live weight increases in the Guinea fowl [15].…”
Section: Discussionsupporting
confidence: 88%
“…The association between body weight and egg weight was similar to the findings of [15] who observed a fairly high association between egg production and weight gain in the Black and Pearl Guinea fowl. This means that point of lay does not terminate live weight increases in the Guinea fowl [15].…”
Section: Discussionsupporting
confidence: 88%
“…The EWF presently is higher than 51.45 and 51.35, g for crossbreds of Dominant black (DB) and Fulani ecotype (FE) chickens (DBxFE and FExDB) reported by Sola-Ojo and Ayorinde (2011); and 48.84g from Potchefstroom (Tadesse et al, 2013); but lower than 58.78 and 60.27, g from IB and BOVAN BROWN hens (Tadesse, 2013). Our findings contradict Render et al, 1984;and Ayorinde et al, 1988; that low body-weight were superior to high body-weight birds in egg production. Our results support Ayorinde and Oke (1995) who reported insignificant differences on egg production traits between heavy and low body weight birds; and Udeh (2007) who observed that rearing birds on weight basis may have no significant advantage, because high and light body weight birds reared in same environment recorded similar results in hen-day egg production within breed.…”
Section: Effect Of Interaction Between Genotype and 20-week Pullet Weightcontrasting
confidence: 96%